Papers - - Production - Foreign - Petroleum Development in Peru during 1935 - Oliver B. Hopkins (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1936)
Peruvian production for the year 1935 amounted to 17,064,879 bbl., a record amount for any year, bringing the cumulative production of the country up to 188 million barrels. The 1935 figure is an increase of 785,769 bbl. over the 1934 total. The property of the International Petroleum Co. contributed 636,812 bbl. of this increase, and the Lobitos property 158,625 barrels. Exploration work in the country was again active, with attention focused on three areas, the Huallaga River, Lake Titicaca and the Coastal Zone of the Province of Tumbes. It is reported that in the Huallaga River area the Selden Breck Construction Co. has completed geological and engineering studies on its Pachitea River concessions and has ordered a drilling rig. In the Lake Titicaca region further studies in the vicinity of Pusi were made by Government geologists. During the period from 1906 to 1915, the Pirin anticline in this area produced 285,936 bbl. of low-grade crude. The Government holds 120,000 hectares of reserved lands in this area. In the Coastal Zone of the Province of Tumbes explorations by the Government were continued on the National Reserve, and a test location has been selected in the Quebrada Zapotal about 10 miles from the Port of Zorritos. An order has been placed in the United States for drilling equipment. LaBrea-Parinas Estate.—Production on the LeBrea-Parinas Estate reached an all-time high in 1935 of 14,756,914 bbl., an increase of 636,812 bbl. over the 1934 record. The total production from 1890 to 1935 was 148,541,523 bbl. During 1935 a total of 63,021 ft. was drilled in new wells and 5449 ft. in deepening existing wells; 23 wells were deepened and 29 new wells were completed, of which 27 were producers and 2 were dry holes. At the end of the year 2873 wells had been drilled on the Estate, of which 1838 were still productive. The remaining 1035 wells represent abandoned producers or dry holes. Practically all the drilling on the property has been done with cable tools, but during 1934 three strings of rotary tools were introduced. Experience with these outfits has shown that rotary equipment can